Penerapan Post Pandemic Design Pada Apartemen Di Masa Sekarang - Suriani Binti Masri; Rahayu, Irma; Nursyam, Nursyam (TIMPALAJA : Architecture Student Journals, 2023)
Abstract_ Post Pandemic Design is how an architect can design or build a design space during this pandemic. In addition, how can an architect design a space usually intended for small groups to quickly and easily accommodate social distancing that does not only reduce occupancy rates? How to find solutions through mechanical systems, lighting, partitions, and furniture, even in circulation. A pandemic is a disease outbreak that occurs simultaneously everywhere, covering a wide geographical area, be it an entire country or continent